2021
DOI: 10.1007/s12671-021-01750-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Mechanisms of Mindfulness Training for School Teachers in Difficult Times: A Randomized Controlled Trial

Abstract: Objectives Research in recent years has shown that mindfulness-based interventions can enhance teachers’ mental and physical health. However, the existing studies were predominantly conducted in Western, educated, industrialized, rich, and democratic (WEIRD) societies. As a randomized controlled trial in a non-WEIRD society, the present study examined the effectiveness and mechanisms of mindfulness training for Hong Kong teachers in difficult times. Methods Teachers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The well-being statuses were negatively related with teachers' intentions to leave, a personal outcome for teachers Teaching Practice Seo & Yuh (2021) Researchers observed that teacher stress affected teacher-student interactions, as part of the teaching practices. Further, mindfulness and resilience could mediate such relationships Tsang et al (2021) In this longitudinal study, one important result was that mindfulness training could enhance teacher well-being, which then prompted teachers' mindfulness in teaching Student Outcome Madigan & Kim(2021) The researchers conducted a systematic review on the consequences of teacher well-being (i.e., burnout) on students' academic achievement and motivation Shoshani ( 2021)…”
Section: Discussionmentioning
confidence: 99%
“…The well-being statuses were negatively related with teachers' intentions to leave, a personal outcome for teachers Teaching Practice Seo & Yuh (2021) Researchers observed that teacher stress affected teacher-student interactions, as part of the teaching practices. Further, mindfulness and resilience could mediate such relationships Tsang et al (2021) In this longitudinal study, one important result was that mindfulness training could enhance teacher well-being, which then prompted teachers' mindfulness in teaching Student Outcome Madigan & Kim(2021) The researchers conducted a systematic review on the consequences of teacher well-being (i.e., burnout) on students' academic achievement and motivation Shoshani ( 2021)…”
Section: Discussionmentioning
confidence: 99%
“…Dahal and Pradhan 2018 [43] Nepal (Asia) Non-RCT This review found 40 articles with sixteen types of interventions for addressing burnout and stress in teachers: (a) 18 studies on mindfulness-based interventions [12,[23][24][25]27,29,[33][34][35][36][37][38][39][40][41] including in combination with yoga [32] or in combination with Cognitive Behavioural Therapy (CBT) [26,42], (b) seven studies reported on CBT only [30,31] or CBT in combination with yoga [22,28], or other derivatives, e.g., Inquiry-Based Stress Reduction (IBSR) [57,60] and Cyclic meditation [43] (c) seven studies used Rational Emotive Behavior Therapy [44][45][46][47][48][49][50], (d) one study on Sports-Based Physical Activity Program [55] (e) Christian prayer and prayer-reflection [52] (f) Group Sandplay [58], (g) stress reduction training (e.g., Stress Management and Resiliency Training Program (SMART) [51], Autogenic Training [59], Progressive Muscle Relaxation with music and aromatherapy [53]), and (h) interventions focusing on building social and emotional competence (e.g., A+ intervention [56], Ability Model of Emotional intelligence…”
Section: Interventions To Reduce Stress and Burnout Among Teachersmentioning
confidence: 99%
“…Four studies were conducted in the UK,14 24–26 seven studies were from the USA,12 13 15 27–30 four from Hong Kong,11 31–33 four studies from Nigeria 34–37. Others were from Spain,38 Australia,39 Netherlands,40 Japan,41 India,42 Germany43 and Poland 44.…”
Section: Resultsmentioning
confidence: 99%